Cathepsin B‐Specific Metabolic Precursor for In Vivo Tumor‐Specific Fluorescence Imaging. (20th October 2016) - Shim, Man Kyu; Yoon, Hong Yeol; Ryu, Ju Hee; Koo, Heebeom; Lee, Sangmin; Park, Jae Hyung; Kim, Jong‐Ho; Lee, Seulki; Pomper, Martin G.; Kwon, Ick Chan; Kim, Kwangmeyung
Abstract: Recently, metabolic glycoengineering with bioorthogonal click reactions has focused on improving the tumor targeting efficiency of nanoparticles as delivery vehicles for anticancer drugs or imaging agents. It is the key technique for developing tumor‐specific metabolic precursors that can generate unnatural glycans on the tumor‐cell surface. A cathepsin B‐specific cleavable substrate (KGRR) conjugated with triacetylated N ‐azidoacetyl‐d ‐mannosamine (RR‐S‐Ac3 ManNAz) was developed to enable tumor cells to generate unnatural glycans that contain azide groups. The generation of azide groups on the tumor cell surface was exogenously and specifically controlled by the amount of RR‐S‐Ac3 ManNAz that was fed to target tumor cells. Moreover, unnatural glycans on the tumor cell surface were conjugated with near infrared fluorescence (NIRF) dye‐labeled molecules by a bioorthogonal click reaction in cell cultures and in tumor‐bearing mice. Therefore, our RR‐S‐Ac3 ManNAz is promising for research in tumor‐specific imaging or drug delivery.